Report on the Working of the Central Government Health Scheme for 1964 - Planning Commission (Planning Commission, 1964)
The year 1964 was yet another year largely of consolidation of the Central Government Health Scheme in Delhi, ""Riis year was however significant, as for the first time the facilities provided by the Scheme were also utilized to provide medical cover to members of public and their families residing in the areas of jurisdiction of eight C.G.H.S. Dispensaries (Moti Bagh, Lakshmibai Nagar, Kidwai Nagar, and Andrews Ganj) with effect from 1st July, 1964 and North Avenue, South Avenue, Constitution House and Chanakyapuri with effect from 28th November, 1964. This is the first time that members of the general public have been brought within the ambit of welfare scheme which was initially reserved exclusively for the Government servants. the response of the public to this measure was slight as only 98 members of the public joined the Scheme during 1964. Further details are shown in Appendix ‘IA’. the success of this venture would to a large extent reflect the responsiveness of the urban public to a comprehensive Health Insurance Scheme.
Government of India